(untitled) (Verba Vitae Unwira, 2020)
This study examines the self-concept of wives who act as breadwinners in families. This study aims to describe the self-identity of the wives and their communication experiences in interacting with their living environment. Fitts’s (1971)’s self-concept theory which includes the self-concept of internal and external dimensions was applied. This study is a phenomenological study that applied a qualitative method. The data were collected through online interviews. Four informants who live in Cikiwul Village of Bantar Gebang District, Bekasi City were selected with a purposive sampling technique. This study uncovers that the self-identity of the wives was constructed based on internal dimensions. As a self-judgment, the informants reported that they have self-satisfaction and accept themselves as breadwinners. They hold high self-esteem. Their communication experiences were influenced by external dimensions. Their environment was supportive of their interactions. This indicates that the wives have developed positive communication experiences with their families and friendswho have supported their choice to be a breadwinner.